Teologi Humanis Jamâl al-Bannâ: Sebuah Rekonstruksi Epistemologis Studi Keislaman - Mukhammad Zamzami (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2012)
This article mainly discusses Jamâl al-Bannâ’s thought, an Egyptian-born Muslim contemporary thinker, who offers humanist theology. As Jamâl observed that the Islamic theology ignores the aspect of humanity, he then tried to fix it to reconstruct the sources and system of Islamic thought into three things, namely the Qur’ân, the Sunnah, and the Hikmah (Wisdom). Each aspect is read through a “new method of reading,” aiming that the stream of Islamic theology will flow more humanist and will be able to synergize with its time. Jamâl’s stream of thought is centered on the aspect of humanity, emphasizing that every product of Islamic thoughts should have a hook with the principles of justice and welfare because that is the main principle of Islamic teachings.